Magnetic properties of some spinel ferrites - Ouaissa, Mohamed (Université Ibn Tofail, Faculté des Sciences-Kénitra, 2016)
The aim of this word was to study the behaviors of the magnetic properties of nickel ferrite (Nife2o4) and magnetite (fe3o4) under the effects of temperature, crystal fields, and exchange interactions using the mean field theory (MFT). By using the mean field approximation with the Gibbs-Bogoliubov inequality, the magnetic behavior of nickel ferrite (NiFe2O4) and magnetite (Fe3o4) was theoretically studied in the absence of an external magnetic field while in the absence and presence of crystal fields for various exchange interactions at each lattice site occupied by a magnetic ion. Below the Curie temperature Tc, magnetic frustration behaviors from the calculations were observedfor nickel ferrite and magnetite. Nife2O4 exhibits ferromagnetic phase with a second order transition to paramagnetic phase. A first order transition was found between magnetic ordered phases at low observed that the magnetite acts as a pure ferrimagnet in the presence of a crystal field of ferric Fe2+ in the octahedral site, while the crystal field of the ferrous Fe3+ is equal to zero. There was a second order transition accompanied with a broken symmetry at high temperature.
Keywords: Spinel; Magnetic; Ferrite.